1973
DOI: 10.1111/j.1365-2621.1973.tb02795.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Low Dose Irradiation to a Fresh Bread System for Space Flights

Abstract: Irradiation pasteurization of flour and bread at 50,000 rads markedly reduced their microflora. Irradiation pasteurization of bread in combination with the irradiated flour extended the period of freedom or low incidence of mold growth when stored at 21–25°C improving the use of fresh bread for flights having several weeks duration. The irradiation process reduced the presence of the mold genera Aspergillus and Penicillium, which suggests an advantage when considering potential toxic metabolites that may resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…However, only a few of them have been tested against toxigenic Aspergillus spp. with majority of the tests being in artificial synthetic media and only Hartung et al (1973) reported that raisin bread containing cinnamon did not support growth and aflatoxin production by A. parasiticus. Similarly, Montes-Belmont and Carvajal (1998) investigated the effect of eleven plant essential oils for maize protection against A. flavus and found out that essential oils of cinnamon (C. zeylanicum), peppermint (Mentha piperita), basil (Ocimum basilicum), thyme (Thymus vulgaris), origanum (Origanum vulgare), flavouring herb epazote (Teloxys ambrosiodes), clove (Syzygium aromaticum) caused a total inhibition of fungal development on maize kernels.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, only a few of them have been tested against toxigenic Aspergillus spp. with majority of the tests being in artificial synthetic media and only Hartung et al (1973) reported that raisin bread containing cinnamon did not support growth and aflatoxin production by A. parasiticus. Similarly, Montes-Belmont and Carvajal (1998) investigated the effect of eleven plant essential oils for maize protection against A. flavus and found out that essential oils of cinnamon (C. zeylanicum), peppermint (Mentha piperita), basil (Ocimum basilicum), thyme (Thymus vulgaris), origanum (Origanum vulgare), flavouring herb epazote (Teloxys ambrosiodes), clove (Syzygium aromaticum) caused a total inhibition of fungal development on maize kernels.…”
Section: Introductionmentioning
confidence: 95%
“…The use of spices in preserving food products has been traditional and they are cultivated in many countries such as India, Japan and Russia (Hartung, Bullerman, Arnold, & Heidelbagh, 1973). Spices occupy a prominent place in the traditional culinary practices and are indispensable part of daily diets of millions of people all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…By applying a 50-krad dose of irradiation to flour and subsequently to bread, Hartung et al (1973) showed a significant reduction in the visible and total mold count, as well as in bacterial count, on bread stored for up to 20 weeks.…”
Section: A Breads 1 Extension Of Shelf Lifementioning
confidence: 97%
“…Hartung et al (1973) reported that the total detectable aerobic bacteria per gram of flour was 600 and 2,400 for irradiated and nonir radiated flour, respectively. The predominant bacteria type was Gram-positive cocci (88%), most of which were Staphylococcus epidermidis.…”
Section: A Breads 1 Extension Of Shelf Lifementioning
confidence: 98%
See 1 more Smart Citation